(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The presented article deals with the analysis of narrative techniques used in the novels of Native American writer Louise Erdrich. In writing her novels the writer makes an effective use of captivity narratives in presenting the history of Native Americans through her novel characters. By using captivity narratives that present good and bad Native Americans, Louise Erdrich changes the images of local Indians and presents her descendants as cultured and caring people who worry about the future of the tribes. Local Indian history, culture, traditions and rituals are introduced and reminded to modern generation of Native Americans through the novels of Louise Erdrich.